2019
DOI: 10.1155/2019/1282085
|View full text |Cite|
|
Sign up to set email alerts
|

Tuina Massage Improves Cognitive Functions of Hypoxic-Ischemic Neonatal Rats by Regulating Genome-Wide DNA Hydroxymethylation Levels

Abstract: In addition to abnormalities of motor and posture, children with cerebral palsy (CP) often have intellectual disability. As a complementary and alternative traditional Chinese medicine (TCM) therapy, Chinese Tuina massage, also called Tuina in China, has been widely applied in clinical treatment for CP in China for a long time. However, the molecular basis for this still remains largely unknown. Recently, DNA hydroxymethylation has been shown to be sensitive to environment and plays critical roles in some neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…As a complementary and alternative traditional Chinese medicine (TCM) therapy, Chinese Tuina massage, also called Tuina in China, is an ancient TCM treatment method. [ 15 ] It is based on the basic theory of TCM as well as the theory of viscera and meridians, combined with the anatomy of western medicine. Manipulation is applied to the specific part of the body surface to regulate physiological and pathological conditions of the body, so as to dredge the channels and collaterals, regulate Qi and blood, dispel pathogenic factors and strengthen health, and harmonize Yin and Yang.…”
Section: Introductionmentioning
confidence: 99%
“…As a complementary and alternative traditional Chinese medicine (TCM) therapy, Chinese Tuina massage, also called Tuina in China, is an ancient TCM treatment method. [ 15 ] It is based on the basic theory of TCM as well as the theory of viscera and meridians, combined with the anatomy of western medicine. Manipulation is applied to the specific part of the body surface to regulate physiological and pathological conditions of the body, so as to dredge the channels and collaterals, regulate Qi and blood, dispel pathogenic factors and strengthen health, and harmonize Yin and Yang.…”
Section: Introductionmentioning
confidence: 99%
“…[ 34 ] Tuina is a traditional form of manipulative therapy, and is essentially a Chinese medical massage. [ 35 , 36 ] The therapeutic effect is achieved by applying a certain force to the muscles or soft tissues of the body through the operator's fingers, hands, elbows, knees, and feet. [ 37 ] Tuina has been shown to have a positive impact in the treatment of constipation.…”
Section: Introductionmentioning
confidence: 99%
“…Tuina, a kind of massage methods, is used as an independent method and as an alternative to traditional and Western treatments [21,22]. Previous studies have indicated that Tuina has been successfully applied to various diseases such as neurological diseases, injuries, rheumatism and other types of diseases [23].…”
Section: Introductionmentioning
confidence: 99%